A comprehensive transcriptome of early development in yellowtail kingfish (Seriola lalandi). (20th August 2015) - Patel, A.; Dettleff, P.; Hernandez, E.; Martinez, V.
Abstract: Seriola lalandi is an ecologically and economically important species that is globally distributed in temperate and subtropical marine waters. The aim of this study was to identify large numbers of genic single nucleotide polymorphisms (SNPs) and differential gene expression (DGE) related to the early development of normal and deformed S. lalandi larvae using high‐throughput RNA‐seq data. A de novo assembly of reads generated 40 066 genes ranging from 300 bases to 64 799 bases with an N90 of 788 bases. Homology search and protein signature recognition assigned gene ontology (GO) terms to a total of 15 744 (39.34%) genes. A search against the Kyoto Encyclopedia of Genes and Genomes Pathway database (KEGG) retrieved 6808 KEGG orthology (KO) identifiers for 10 520 genes (26.25%), and mapping of KO identifiers generated 337 KEGG pathways. Comparisons of annotated genes revealed that 1262 genes were downregulated and 1047 genes were upregulated in the deformed larvae group compared to the normal group of larvae. Additionally, we identified 6989 high‐quality SNPs from the assembled transcriptome. These putative SNPs contain 4415 transitions and 2574 transversions, which will be useful for further ecological studies of S . lalandi . This is the first study to use a global transcriptomic approach in S. lalandi, and the resources generated can be used further for investigation of gene expression of marine teleosts to investigate larval developmental biology. The results of the GO enrichment analysis highlight the crucial role of the extracellular matrix in normal skeleton development, which could be important for future studies of skeletal deformities in S. lalandi and other marine species.